DESIGN AND BUILD A MODEL OF A MARINE WAVE POWER PLANT ENGINE FOR EDUCATIONAL TEACHING AIDS - Oki Fajar Satriawan; Muhamad Safi’I; Althesa Androva (International Journal of Multidisciplinary Reseach, 2026)
Renewable energy sources have been widely developed to reduce the consumption of non-renewable energy. However, an energy source that is still underutilized but has significant potential is ocean wave energy, which utilizes lift energy to operate generators that generate electricity. The machine is designed to develop a model that converts water wave energy into electrical energy on a laboratory scale and to examine the correlation between water wave energy and electrical energy generated by changing the length of the float arm. The methodology used in this final project is a literature review to gather information relevant to water waves and electricity-generating machines. Machine design and component manufacturing include making alternative designs, selecting designs, then testing whether there is a linear output and analyzing the relationship between water waves and the electricity output produced. The results of the experiment showed that the largest electrical output was obtained at an arm length of 40 cm with an average electrical power generated of 1,019 watts. Testing on PLTGL components was carried out with variations in the length of the buoyancy arm of 40 cm, 45 cm, and 50 cm.